2004
DOI: 10.1002/j.2050-0416.2004.tb00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence Identities ofhorAHomologues and Adjacent DNA Regions Identified in Three Species of Beer-Spoilage Lactic Acid Bacteria

Abstract: J. Inst. Brew. 110(4), 276-283, 2004The horA homologues and adjacent DNA regions identified in beer-spoilage Lactobacillus lindneri DSM 20690 T and L. paracollinoides DSM15502 T were examined and compared with the corresponding DNA region of beer-spoilage L. brevis ABBC45, a strain in which the hop-resistance gene horA was originally identified. The PCR analysis suggests ORFB1-B5 regions surrounding horA are conserved in all of the strains. The nucleotide sequence comparison of the conserved DNA regions reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 24 publications
(43 reference statements)
0
33
2
Order By: Relevance
“…This type of beer is representative of beers with standard microbiological stability. Although nine horA-positive strains were recognized as false-positive strains in this investigation, four L. brevis strains and one L. casei strain were able to grow in beers adjusted to pH 4.6, which represent beers with weak microbiological stability 100 . Depending on the types of beers manufactured, these false-positive strains should be considered as spoilage strains.…”
Section: Identification Of the Second Hop Resistance Gene Horcmentioning
confidence: 74%
See 3 more Smart Citations
“…This type of beer is representative of beers with standard microbiological stability. Although nine horA-positive strains were recognized as false-positive strains in this investigation, four L. brevis strains and one L. casei strain were able to grow in beers adjusted to pH 4.6, which represent beers with weak microbiological stability 100 . Depending on the types of beers manufactured, these false-positive strains should be considered as spoilage strains.…”
Section: Identification Of the Second Hop Resistance Gene Horcmentioning
confidence: 74%
“…It was further shown that a small number of L. paracollinoides strains are able to grow in beer despite the absence of horA homologs, indicating multiple genetic markers are required for the concept of trans-species genetic markers to be practically applied in breweries 100 .…”
Section: Discovery Of the Hop Resistance Gene Horamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the potential applications of these genetic markers have been suggested to the comprehensive species-independent identification of beer-spoilage LAB strains. The horizontal transfer hypothesis of hop-resistance genes has been based on the sequence identities of the horA and horC-carrying DNA regions found in L. brevis, L. lindneri, L. paracollinoides and P. damnosus 17,[22][23][24] . Therefore we attempted to characterize the horA and horC-containing DNA regions in P. inopinatus and L. backi.…”
Section: Analysis Of the Hora-containing Regions And The Horc-containmentioning
confidence: 99%